계획수립 사용자 중심의 기후적응 의사결정지원 시스템 - 현정희(Hyun, Jung Hee); 김지연(Kim, Ji Yeon); 이동근(Lee, Dong Kun); 허주영(Huh, Ju Young); 배채영(Bae, Chae Young); 정휘철(Jung, Huicheul); 정태용(Jung, Tae Yong); 차동호(Cha, Dong Ho) (한국기후변화학회지, 2020)
The extent to which climate information is used to support decision-making remains unclear for various adaptation planning contexts. Recent research efforts have sought to better understand the needs and requirements of users to better format climate information to relevant parameters. This study examines the development of practice-driven climate change services in South Korea’s adaptation planning based on self-reviews and interviews. A review of current research trends confirmed the need for integrated, flexible, collaborative, and decision-driven climate services. Combining the two findings, we outline and describe the resulting climate change adaptation planning decision support system (ADAPT-Ko) made available for South Korea’s adaptation planners. KCI Citation Count: 0